Caleosin expression enhances plant insect resistance - Sakihito Kitajima; Toshiharu Akino; Hideki Yoshida; Kenji Miura; Toki Taira; Eric Hyrmeya Savadogo; Naoki Tani (Current Plant Biology, 2025)
This study investigated the anti-insect activity of the caleosin homolog CLO3, which accumulates in the latex of Euphorbia tirucalli (Euphorbiaceae). Nicotiana benthamiana leaves transiently producing EtCLO3 were fed to Spodoptera litura (Lepidoptera) larvae, and their body weights were recorded. The production of EtCLO3 significantly retarded larval growth. Similar effects were observed with other plants’ caleosin homologs that share unique N-terminal motifs located upstream of the Ca2 + -binding EF-hand, including Arabidopsis thaliana CLO3 (AT2G33380) and homologs from lower plants (liverworts Mapoly0027s0099 and Chlamydomonas Cre06.g273650_4532). In contrast, A. thaliana CLO5 (AT5G19530), which belongs to a different class of caleosins, did not exhibit this growth retardation effect. Notably, the anti-insect activity of EtCLO3 persisted even when mutated in its peroxygenase catalytic site or EF-hand. A transcriptome analysis revealed that EtCLO3 up-regulated endogenous defense-related gene expression levels and altered sugar metabolism pathways. These findings suggest that EtCLO3 may, at least in part, exert its anti-insect effects by activating the host plant’s endogenous defense system. This research provides insights into how EtCLO3 and some other homologs influence larval development and suggests potential applications for these proteins in pest management.